Vesicles and particles of sodium bis(2-ethylhexyl) phosphate in binary and ternary systems - Nakache, Evelyne; Bouloussa, Otman; Bourguet, Jacques; Lovera, Jacqueline; Gregiore, Pierre (Biochimica et biophysica acta, 1991)
Vesicles were identified in aqueous solution of pure sodium bis(2-ethylhexyl) phosphate, a short branched chain surfactant. Superficial tension measurements show that the vesicles appear above a molality of 0.02 (0.69 %w). These aggregates are equilibrium structures. The ‘packing parameter’ theory established by Israelachvili et al. allows the prediction of the occurrence of such vesicles. If an organic solvent, such as xylene or ethylhexanoate, is added to the binary system, a different type of aggregate appears, the size of which is determined by several methods including electron microscopy and light scattering. Interfacial tension measurements show that these aggregates would be expected to form above a molality of 0.02. According to our experimental results, the microstructure of these aggregates can be described as micelles and/or vesicles, swollen or not.